Filipino adolescents' online computer game playing experiences and parental monitoring - Dimla, Mary Grace Cruz
The study aims to describe the online computer gaming experiences of adolescents and determine the presence or absence of parental monitoring on the said activity. Survey and focus group discussions were conducted in UP Integrated School among 81 adolescents whose age ranges from 13 to 16 years old. The adolescents play three kinds of online computer games wherein the most popular are Massively Multiplayer Online Role Playing Games (MMORPG). They identified 75 different online computer games in which the most frequently played was Defense of the Ancient or DOTA. On the average, they play three different games in their house, thrice a week for a minimum of two hours each session and spend P21.00-P30.00 on computer rentals. Males choose more violent and challenging kinds of games compared to females who prefer easier games. On parental monitoring, 92% of the adolescents reported their parent are aware of their online computer game activity. The same parents allow them to play online computer games for unlimited hours in their house. Moreover, 52% of these parents are concerned with the time spent on playing and used verbal checking to monitor this activity. However, 48% do not provide attention for monitoring adolescent's activities on online computer games. They only intervene when problems on academic performance and negative behaviors arise. Overall, only 8% reported their parents are not aware they play online computer games. Reasons include avoidance of punishment while some believe it is irrelevant to inform their parents. Generally, there is a high degree of parental monitoring but it does not deter playing online computer games; rather it only posts an action that tries to eliminate negative outcomes among the players. Further studies may explore parental monitoring both from parents and adolescents, and expand the scope of study to include samples from the lower socio-economic class and rural areas.